CO2 ABSORPTION AND O2 PRODUCTION BASED ON NDVI – FVC IN ABEPURA DISTRICT IN 2020 – 2024 - Kusumah A.Y. Arya; Amal S.A (RADJA PUBLIKA, 2025)
This study maps and analyzes the spatial-temporal distribution of vegetation functions as carbon dioxide (CO₂) absorbers and oxygen (O₂) producers in Abepura District, Jayapura City, for the period 2020–2024 using remote sensing and Geographic Information Systems (GIS) approaches . Estimation is carried out through the calculation of NDVI ( Normalized Difference Vegetation Index ) which is derived into Fractional Vegetation Cover ( FVC ), then used to estimate Net Primary Productivity ( NPP ) and converted into CO₂ absorption and O₂ production. The mapping results show a range of CO₂ absorption values of 0.001–3.67 kg/m²/year and O₂ production of 0.001–2.679 kg/m²/year, with maximum values that tend to be stable between years but there are changes in distribution in the low to medium classes which indicate the dynamics of vegetation regulation capabilities. The highest values are generally concentrated in areas with dense vegetation cover, while the lowest values are found in built-up areas. These results underscore the importance of remaining green space in supporting urban climate regulation and form the basis for recommendations for green infrastructure planning and vegetation conservation strategies in areas experiencing urban pressure.